An illustrated guide to lady beetles (Coleoptera: Coccinellidae) of the Indian Subcontinent. Part 1. Tribe Coccinellini - Poorani, J. (Zootaxa, 2023)
An illustrated guide to the tribe Coccinellini (Coleoptera: Coccinellidae: Coccinellinae) of the Indian Subcontinent comprising 119 species of 30 genera is presented. Brief diagnostic accounts of the genera and the species included therein are given with supporting illustrations of diagnostic characters, including genitalia, wherever available. Details of distribution, prey and plant associations, and seasonal occurrence are provided based on collections, label data and literature. For 31 species, illustrations of the life stages are included to facilitate the field identification of the immature stages. Adalia puetzi Iablokoff-Khnzorian, 1986 is synonymized with Adalia simmondsi Kapur & Sudha Rao, 1962 (new synonym). Oenopia smetanai Canepari, 1997 is removed from synonymy with O. flavidbrunna Jing, 1986 and restored as a valid species (status revised). Illeis kapuri Anand, Gupta & Ghai is transferred to Ortalia Mulsant, 1850 (new combination). Two new species, Harmonia andamanensis sp. n. and Phrynocaria prathapani sp. n. are described and illustrated from the Andamans and the Western Ghats, respectively. Coelophora lushuiensis (Jing, 1992) is documented as a new record for India (Manipur). An updated checklist of the Coccinellini of the Indian Subcontinent is also provided.